2013
DOI: 10.1200/jco.2012.43.8622
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 1 Gene Amplification Is Associated With Poor Survival and Cigarette Smoking Dosage in Patients With Resected Squamous Cell Lung Cancer

Abstract: FGFR1 amplification is an independent negative prognostic factor in surgically resected SCCL and is associated with cigarette smoking in a dose-dependent manner. FGFR1 amplification is a relevant therapeutic target in Asian patients with SCCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 28 publications
7
126
3
Order By: Relevance
“…Recently a meta-analysis showed that patients with FGFR gene amplification have a worse prognosis than FGFR wild-type patients. This gene alteration is also observed in other tumors like breast cancer (14%), urothelial cancer (7%) and ovarian cancer (5%) and squamous cell lung cancer (SCCL) (18.2%) Craddock et al, 2013;Heist et al, 2012;Kim et al, 2016a;Kim et al, 2016b;Monaco et al, 2016). In lung squamous cell carcinoma the presence of FGFR1 amplification doesn't change the patients' prognosis (Craddock et al, 2013).…”
Section: Fgfr In Cancermentioning
confidence: 82%
See 2 more Smart Citations
“…Recently a meta-analysis showed that patients with FGFR gene amplification have a worse prognosis than FGFR wild-type patients. This gene alteration is also observed in other tumors like breast cancer (14%), urothelial cancer (7%) and ovarian cancer (5%) and squamous cell lung cancer (SCCL) (18.2%) Craddock et al, 2013;Heist et al, 2012;Kim et al, 2016a;Kim et al, 2016b;Monaco et al, 2016). In lung squamous cell carcinoma the presence of FGFR1 amplification doesn't change the patients' prognosis (Craddock et al, 2013).…”
Section: Fgfr In Cancermentioning
confidence: 82%
“…Sinapsine, an alkaloid derived from cruciferous' seeds, downregulates FGFR4 (Guo et al, 2016). FGFR resistance to AZD3437 has been found in lung cancer cell lines (H1581AR) due to MET amplification by activating ErbB3, in the same experiment, Kim et al found that a combination of a FGFR inhibitor and a Met inhibitor synergistically inhibited cell proliferation (Kim et al, 2016a;Kim et al, 2016b). In a small cell lung cancer group of patients with FGFR1 amplification treated with Nintedanib might occur a resistance.…”
Section: Resistance To Therapiesmentioning
confidence: 96%
See 1 more Smart Citation
“…FISH has been the most frequently used method to detect FGFR1 amplification status, 9,10,21,22,[25][26][27] although alternative methods such as real-time polymerase chain reaction 24 and SISH 23 have also been used. SISH has several advantages over FISH including automation, use of bright-field microscopes in contrast to expensive FISH microscopes, signal permanence, and easier histologic comparison.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 FGFR1 amplification has recently been reported by members of our group in oral squamous cell carcinoma, 15 but it has also been described in esophageal squamous cell carcinoma, ovarian cancer, bladder cancer, prostate cancer, and rhabdomyosarcoma. [16][17][18][19][20] Subsequent to the landmark initial studies, 9,10 other groups [21][22][23][24][25][26][27] have investigated FGFR1 amplification in non-small cell lung carcinoma, using different definitions of FGFR1 amplification generally utilizing FISH, but there have been reports utilizing silver in situ hybridization (SISH) 23 and real-time polymerase chain reaction. 24 The frequency of FGFR1 amplification in squamous cell carcinoma and its potential as an actionable molecular target highlight the importance of not only defining amplification but also determining the most reliable and reproducible method to detect its presence, as well as assessing which tumor subtypes to test.…”
mentioning
confidence: 99%